Mechanical properties of superplastic thin boronised duplex stainless steel (DSS) - Sultan, N.M.; Jauhari, Iswadi; Sabri, Mohd Faizul Mohd (IOP Publishing, 2019)
A thin 'dog-bone' shape plate of thermo-mechanically treated duplex stainless steel (DSS) was superplastically boronised in compression for 1 and 6 h in a specially designed clamp at 1223 K. Specimens were characterized with XRD, SEM, FESEM, hardness test and tensile test. Substrate microstructures were fine and equiaxed with average grain sizes of 2.996 ±m 0.888 μm and 3.616 ±m 0.855 μm for 1 and 6 h SPB DSS, respectively obeying superplastic characteristics. Two thick and uniform sides of the boronised layer with a thickness range of 26 to 51 μm obtained having a surface hardness of 1768 and 2209 HV after being boronised for 1 and 6 h. The ultimate tensile strength (UTS) values declined from 688 to 427 MPa as boronising time increased, while the toughness and fracture strain values also followed the same trend. Meanwhile, a fracture surface analysis carried out to understand the basis of the UTS, toughness and fracture strain values reduction, revealed that boronising affected the mode of fracture from ductile-dimple to mix ductile and brittle-transgranular and intergranular. An increase in the boronising time and boronised layer thickness led to a decline in the UTS, toughness, and fracture strain values of boronised DSS. In addition, destruction on the opposite side of the boronised layer also contributed to the decline in tensile strength. In order to achieve good mechanical properties in the tensile direction (UTS, fracture toughness, and fracture strain), the thickness of the boronised layer must be kept low. On the other hand, for good mechanical properties in compressive direction (surface hardness) can be achieved with a thick boronised layer. SPB thin DSS shall be stand-alone lightweight materials or combined with other materials through diffusion bonding or cladding for multifunctional properties. © 2019 IOP Publishing Ltd.